The GAMBARAN PEMERIKSAAN SEROLOGI IgM DAN IgG PADA PASIEN DEMAM BERDARAH DENGUE DI RSUD dr. H. MOCH. ANSARI SALEH BANJARMASIN TAHUN 2021-2023 - Amalia, Atqiya Elma; Yahya, Yudi; Perdani, Rizki (Politeknik Unggulan Kalimantan, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus. The virus is transmitted through the bite of female mosquitoes, especially Aedes aegypti and Aedes albopictus species infected with human blood in the viremia stage. The exact diagnosis of DHF is established based on serological examinations, one of which is IgM and IgG examinations. This examination is needed to distinguish fever caused by dengue virus or fever by other causes and this study was to determine the picture of serological examination of Igm and IgG in patients in patiens with Dengue Hemorrhagic Fever at dr. H. Moch Ansari Saleh Regional General Hospital Banjarmasin. This type of research is quantitative descriptive research. The samples used were secondary data from hospitalized DHF patients in 2021-2023 who performed IgM and IgG serological examinations totaling 95 patients. Of the 95 patients, 8 patients (9%) were IgM+ and IgG-, 60 patients (63%) were IgM- and IgG+, 6 patients (6%) were IgM+ and IgG+, 21 patients (22%) were IgM- and IgG-. With this, the results show that the IgM and IgG images in DHF patients are mostly obtained with IgM- and IgG+ serologic test results which are secondary dengue infections.